Testing Device for Metro Vehicle SIV Controller - YU Chang-chao; TAN Li-hong; CHENG Hong-chao; YAN Wei-guang (机车电传动)
A testing device for metro vehicle SIV controller was developed in this paper. The general situation of testing device for SIV controller was firstly introduced, then hardware design of testing device was analyzed emphatically, and software design of testing device was expounded, test procedure was given at last. The testing device had been applied in HongKong metro and worked well.